A prevalência do negociado sobre o legislado: análise da Lei nº. 13.467/2017 frente ao princípio da vedação do retrocesso social - Mello, Gabriela Damschi de (2020)
This study will address the issue of making rights more flexible labor. After all, with the entry into force of the Labor Reform (Law no. 13.467/17), the possibility of of prevalence of what is agreed upon over what is legislated, in the matters provided for in art. 611-A of the CLT. It turns out that such a device, by providing in an exemplary list, the rights that would remain authorized to be made more flexible, through agreements and collective labor agreements, which will prevail over the legislation. This fact ended up authorizing the increase, reduction and even the suppression of workers' rights through negotiations with unions. To this end, using the hypothetical-deductive method, in a theoretical contextualization based on Bibliographic Research techniques. The main objective of this work is to carry out an analysis of the of the aspects in which it is possible to consider or not a social setback, given the prevalence of what is agreed over what is legislated as provided for in the articles 611-A and 611-B of the CLT. Therefore, it appears from the analysis carried out in this dissertation that flexibility in labor legislation matters in a social setback, since the parties are not on equal terms to compromise without State intervention.